Lung function and exercise capacity 6 months after hospital discharge for critical COVID-19 - Kattainen Salla; Lindahl Anna; Vasankari Tuula; Ollila Henriikka; Volmonen Kirsi; Piirilä Päivi; Kauppi Paula; Paajanen Juuso; Kreivi Hanna-Riikka; Ulenius Linda; Varpula Tero; Aro Miia; et al. (BMC, 2022)
Background
The significant morbidity caused by COVID-19 necessitates further understanding of long-term recovery. Our aim was to evaluate long-term lung function, exercise capacity, and radiological findings in patients after critical COVID-19.
Methods
Patients who received treatment in ICU for COVID-19 between March 2020 and January 2021 underwent pulmonary function tests, a 6MWD and CXR 6 months after hospital discharge.
Results
A restrictive ventilatory defect was found in 35% (23/65) and an impaired diffusing capacity in 52% (32/62) at 6 months. The 6-minute walk distance was reduced in 33% (18/55), and 7% (4/55) of the patients had reduced exercise capacity. Chest X-ray was abnormal in 78% (52/67) at 6 months after hospital discharge.
Conclusion
A significant number of patients had persisting lung function impairment and radiological abnormalities at 6 months after critical COVID-19. Reduced exercise capacity was rare.